INNOVATIVE METHODS FOR DEVELOPING CREATIVE SKILLS IN VISUAL ARTS FOR 5TH–7TH GRADE STUDENTS - Tog‘aev Keldiyor Xamidovich, (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article explores innovative methods for developing creative skills in visual arts lessons for students in grades 5–7. The study emphasizes the importance of interactive teaching strategies, problem-solving assignments, and the use of diverse artistic materials to enhance students’ imagination, artistic expression, and critical thinking. Practical recommendations are provided for integrating these methods into classroom practice to foster students’ creativity and engagement.